2022
DOI: 10.2118/209212-pa
|View full text |Cite
|
Sign up to set email alerts
|

Fluid Behavior in Clay-Hosted Nanopores with Varying Salinity: Insights into Molecular Dynamics

Abstract: Summary Clays, with their charged surfaces, are characterized by strong interactions with dissolved ions in brines and injected water. While there is a considerable body of research devoted to clay swelling, little to no progress has been made on fluid distributions and their impact on transport through clay pores when exposed to fluids of varying salinity. In this work, we use a molecular dynamics (MD) approach to characterize fluid distributions when oil and brine with varying salinities are p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 93 publications
2
4
0
Order By: Relevance
“…In addition, the increasing concentration leads to a more uniform water distribution, which expands across the kerogen surface. This observation aligns with the simulation studies by Zhao, Xiong 44 , 45 , and the experimental works by Teklu and Wang 46 , 47 . This observation is evident in three axes, as shown in Fig.…”
Section: Resultssupporting
confidence: 91%
“…In addition, the increasing concentration leads to a more uniform water distribution, which expands across the kerogen surface. This observation aligns with the simulation studies by Zhao, Xiong 44 , 45 , and the experimental works by Teklu and Wang 46 , 47 . This observation is evident in three axes, as shown in Fig.…”
Section: Resultssupporting
confidence: 91%
“…Molecular dynamics (MD) simulation has been extensively applied to understand the dynamics behaviors of gas molecules on the nanoscale. , MD simulations can provide the information on the gas transport characteristic within nanopores taking into account the radical ambient conditions (e.g., high pressure and low temperature). , In previous studies, the different gas–water two-phase flow models in the hydrophobic nanopore or the hydrophilic nanopore had been constructed by MD simulation. Also, the effects of pore surface properties, water concentration, and the gas–water two-phase velocity on the two-phase flow behaviors were reported. The flows of these MD simulations were driven by an external force. Zhang et al reported the two-phase flow process of CH 4 –H 2 O in a silica nanopore by a new method “nanomanometer” using MD simulation.…”
Section: Introductionsupporting
confidence: 77%
“…Through the Water Bridge. H-bond interaction has been reported to be a significant impact on the occurrence of water in silica nanopores 74 (recent work indicated that the salinity of formation water can also change the behavior of the water bridge 75 ). To reveal the microscopic mechanism of CO 2 breaking through the water bridge, we analyzed the effects of CO 2 on H-bond structure and dynamics.…”
Section: Microscopic Mechanism Of Co 2 Breakingmentioning
confidence: 99%